On becoming a teen mom : life before pregnancy - Erdmans, Mary Patrice; Black, Timothy (Oakland, California : University of California Press, 2015)
"In 2013, the New York City Public Health Department placed public service announcements on trains and buses and at transportation stops that showed photos of frowning or crying children saying such things as 'I'm twice as likely not to graduate high school because you had me as a teen' and 'Honestly, Mom ... Chances are he won't stay with you. What happens to me?' Campaigns like this support a public narrative that portrays teen mothers as threatening the moral order, bankrupting state coffers, and causing high rates of poverty, incarceration, and school dropout. These campaigns demonize teen mothers but tell us nothing about their lives before they became pregnant. In this myth-shattering and often deeply disturbing book, sociologists Mary Patrice Erdmans and Timothy Black tell the life stories of 108 brown, white, and black teen mothers. They expose the problems that cause distress in these young women's lives and that are often overlooked in pregnancy prevention campaigns. Some stories are tragic and painful, marked by child sexual abuse, partner violence, and school failure. Others are less devastating, depicting 'girl next door' characters whose unintended pregnancies expose their lack of contraception and unwillingness to abort. Offering a fresh critical perspective on the links between early childbirth and social inequalities, On Becoming a Teen Mom demonstrates how the intersecting hierarchies of gender, race, and social class shape the personal stories of young mothers"--Provided by publisher.
Introduction: the backstory to the baby -- The distraction -- Young young mothers -- Child sexual abuse -- Violence against women -- Education -- Contraception and abortion -- Conclusion: getting beyond the distraction.
Includes bibliographical references (pages 285 -317) and index.
Keywords: Teenage pregnancy -- United States; Teenage girls -- United States -- Social conditions; Teenage girls -- Social conditions; Teenage pregnancy